The impact of COVID-19 on memory: Recognition for masked and unmasked faces - Guerra, Natália; Pinto, Raquel; Mendes, Pedro S.; Rodrigues, Pedro F. S.; Albuquerque, Pedro B. (Frontiers in Psychology, 2022)
Considering the current state of the worldwide pandemic, it is still common to encounter people wearing face protection masks. Although a safety measure against COVID-19, face masks might be compromising our capacity for face recognition. We conducted an online study where 140 participants observed masked and unmasked faces in a within-subjects design and then performed a recognition memory task. The best performance was found when there were no masks either at study and test phase, i.e., at the congruent unmasked condition. The worst performance was found for faces encoded with a mask but tested without it (i.e., masked-unmasked incongruent condition), which can be explained by the disruption in holistic face processing and the violation of the encoding specificity principle. Interestingly, considering the unmasked-masked incongruent condition, performance was probably affected by the violation of the encoding specificity principle but protected by holistic processing that occurred during encoding.